Legislative bargaining with private information: experimental evidence comparing unanimity and majority rule - Piazolo, David; Vanberg, Christoph (Journal of economic behavior & organization, 2025)
This paper experimentally investigates behavior in a legislative bargaining game with private information. A single proposer is seeking to pass a proposal. In each of two rounds, she attempts to buy the necessary votes by offering payments. Between rounds, the game ends in breakdown with a certain probability. The two responders hold privately known disagreement values. We compare behavior under majority (one vote needed) vs. unanimity (both votes needed) rule. The main theoretical prediction is that responders are more “expensive” in round 1 under unanimity rule because there exists a signaling incentive to vote “no”. Under majority rule, this incentive is absent and in fact, responders should fear being excluded after voting “no”. Our experimental findings confirm the presence of signaling incentives under unanimity rule, resulting in lower agreement probabilities than under majority rule. In contrast, the experimental evidence under majority rule is mixed and does not fully coincide with the theoretical predictions.